2021
DOI: 10.3389/fpls.2021.669565
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Physiological Analysis Reveal That α-Linolenic Acid Biosynthesis Responds to Early Chilling Tolerance in Pumpkin Rootstock Varieties

Abstract: Climate changes especially chilling stress affects cucurbit crops during winter seasonal production. Grafting to pumpkin rootstocks is widely used to improve the vigor of cucurbits, especially cucumber (Cucumis sativus L.) plants, in the face of chilling stress. In our study, multi-disciplinary aspect approaches were used to investigate growth changes of pumpkin under chilling stress. Firstly, the morphological and physiological characteristics of 14 pumpkin (Cucurbita moschata) varieties following different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…As is well known, when plants are subjected to external cold stress, the carbohydrate assimilation rate will be reduced, accompanied by reduced efficiency of the calvin cycle [ 53 ] and decreased fluidity of the plasma membrane, which is easily destroyed [ 54 56 ], resulting in an increase in membrane permeability, relative electrolyte leakage, and intracellular ion imbalance [ 57 ]. In this respect, our results indicated that lipid metabolism is the first player in the chilling response in Csa/Cmo and Cmo/Csa heterografts compared with Csa/Csa homografts [ 29 , 58 62 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As is well known, when plants are subjected to external cold stress, the carbohydrate assimilation rate will be reduced, accompanied by reduced efficiency of the calvin cycle [ 53 ] and decreased fluidity of the plasma membrane, which is easily destroyed [ 54 56 ], resulting in an increase in membrane permeability, relative electrolyte leakage, and intracellular ion imbalance [ 57 ]. In this respect, our results indicated that lipid metabolism is the first player in the chilling response in Csa/Cmo and Cmo/Csa heterografts compared with Csa/Csa homografts [ 29 , 58 62 ].…”
Section: Discussionmentioning
confidence: 97%
“…Chilling treatment was performed as described in a previous study [ 29 ]. Briefly, at 7 days after grafting, around 100 seedlings of each graft combination were transferred into a light incubator under a chilling stress condition (4°C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Watermelon ( Citrullus lanatus ) is an important horticultural crop belonging to the Cucurbitaceae family and cultivated worldwide. Grafting is widely used in horticulture production to enhance abiotic/biotic stress resistance, promote water and fertilizer absorption, increase yield, and improve fruit quality ( Lee et al, 2010 ; Schwarz et al, 2010 ; Migicovsky et al, 2019 ; Liu et al, 2021 ). Our previous research indicated that arginine biosynthesis contributes to pumpkin rootstock-induced chilling tolerance ( Shi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%